Unique Case of Alpha 1-Antitrypsin Deficiency Causing Decreased Protein-C and S Activity Leading to DVT and Pulmonary Embolism - Singla, Manoj (Edelweiss Applied Science and Technology, 2018)
Although Alpha-1 Antitrypsin Deficiency (AATD) is generally considered to be rare, estimates that 80,000 to 100,000 individuals in the United States have severe deficiency of AAT suggest that the disease is under-recognized. The prevalence of AAT varies considerably from one country to another; however, it is estimated that more than 3 million people worldwide have allele combinations associated with severe deficiency of AAT The pathogenesis of the liver disease is quite different and is called a "toxic gain of function." The liver disease results from the accumulation within the hepatocyte of unsecreted variant AAT protein. Only those genotypes associated with pathologic polymerization of AAT within the endoplasmic reticulum of hepatocytes (eg, PI*ZZ type AATD) produce disease. Most patients with liver disease due to AATD are homozygous for the Z allele (ie, PI*ZZ); liver disease does not occur in null homozygotes who have severe deficiency of AAT, but no intra-hepatocytic accumulation.